PENILAAN PERUSAHAAN PT XL AXIATA, TBK DENGAN METODE DISCOUNTED CASHFLOW - , Made Bagus Stiawan Adhi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
An valuation of a company is an important step in maintaining the continuity of the company because the company valuation may provide the trigger for investors to invest their capital, thus indirectly to maintain the credibility of the company. The method used in this study is the discounted cash flow. discounted cash flow technique is one assess a company that has a fairly high degree of accuracy because of the assumptions into account in detail. In addition, DCF is also a technique of assessing the cash flows received in the future into the present value of the expected interest rate investors. This study aims to find out what is the company's value and intrinsic value / fair value of PT. XL Axiata, Tbk if calculated using the discounted cash flow method. In addition, if the value of the stock market today can be overvalued or undervalued when compared to the intrinsic value / fair obtained from the calculation using the projected financial statements. Overvalue or undervalue a stock price in the stock market should certainly be no comparison to the price at which the stock price in the stock market does not reflect the value of the company at that time. In looking for a value comparison, can be done from the internal side of the company because it is necessary to know the price conditions that are considered in accordance with the value of the company.